2013
DOI: 10.3390/en6126242
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different CH4-CO2 Replacement Processes in Hydrate-Bearing Sediments by Measuring P-Wave Velocity

Abstract: Abstract:The replacement of methane with carbon dioxide in natural gas hydrate-bearing sediments is considered a promising technology for simultaneously recovering natural gas and entrapping CO 2 . During the CH 4 -CO 2 replacement process, the variations of geophysical property of the hydrate reservoir need to be adequately known. Since the acoustic wave velocity is an important geophysical property, in this work, the variations of P-wave velocity of hydrate-bearing sediments were measured during different CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Positive synergy between optimized flow control and guest molecule replacement may therefore be achieved through binary gas injection. However, sonic measurements on samples have detected loss of stiffness during the replacement process [24,39]. This has also been supported by observed resistivity trends [33], which indicates rearrangement or decomposition of hydrates during binary gas injection.…”
Section: Flow Remediation Through Binary Gas Injectionmentioning
confidence: 54%
See 2 more Smart Citations
“…Positive synergy between optimized flow control and guest molecule replacement may therefore be achieved through binary gas injection. However, sonic measurements on samples have detected loss of stiffness during the replacement process [24,39]. This has also been supported by observed resistivity trends [33], which indicates rearrangement or decomposition of hydrates during binary gas injection.…”
Section: Flow Remediation Through Binary Gas Injectionmentioning
confidence: 54%
“…46% recovery was observed after injecting 1 PV CO2, which is 53% higher than observations for samples at 4 °C. Liu et al [24] studied exchange performance at various temperature and reported similar ultimate recovery although (Sw/Sh) the replacement rate was higher at elevated temperature. We have observed both higher exchange rate and final recovery (10%) in this study.…”
Section: Continuous Co2 Mass Transport In Non-fractured Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang et al [22] proved that the P-wave velocity and amplitude of the hydrate-bearing sediments behave in the same way and decrease slightly because of the dissociation of CH 4 hydrate when free CH 4 gas is released and CO 2 gas is injected. Liu et al [23] also found that the P-wave velocity continually decreased during all replacement processes. Hyodo et al [24] confirmed that newly formed CO 2 hydrate would keep the reservoir mechanically stable when CH 4 -CO 2 replacement took place in a relatively short period of time in sediments formed by Toyoura sand.…”
Section: Introductionmentioning
confidence: 89%
“…More CH4 hydrate was dissociated than CO2 hydrate due to their dynamic stability differences, which decreased the strength of the sample [31]. show clearly that the failure strength of the CO 2 hydrate-bearing sediments is higher than that of the CH 4 hydrate sediments under different confining pressures, and CH 4 -CO 2 replacement is beneficial to the stability of the reservoir [23,24]. Besides this, in the shear process, the strength of the hydrate-bearing sediments may consist of the strength of ice, hydrate, and sediment matrix and their interaction [29].…”
Section: The Effect Of Confining Pressurementioning
confidence: 94%